Fotodynamická terapie s verteporfinem: od neovaskularizace k hemangiomu aneb kdyz sítnice makulou nekoncí - Soucek, P; Soucková, I (Ceska a slovenska oftalmologie, 2010)
There was a 10-years anniversary from the introduction of photodynamic therapy (PDT) with verteporfin in the Czech Republic recently. We still follow one of our first patients with neovascular macular degeneration. Although it was possible to stabilize the vision of the better eye almost 3 times longer compare to a natural history of the disease on the fellow eye, the final result on both eyes today is identical and below the legal blindness range.We use PDT as a monotherapy for example in management of choroidal hemangioma now-a-days as two next cases show. There were lesions localized peripapillary and bigger than the maximum laser spot size respectively. So called "floating spot" was performed--principle of which we had published previously elsewhere.
Keywords: senioři; Verteporfin; Fluorescein Angiography; fluoresceinová angiografie; nádory choroidey; porfyriny; Porphyrins; mladiství; Middle Aged; Macular Degeneration; mužské pohlaví; fotochemoterapie; Choroid Neoplasms; verteporfin; Hemangioma; Choroidal Neovascularization; ultrasonografie; ženské pohlaví; Humans; makulární degenerace; Photochemotherapy; lidé středního věku; Ultrasonography; hemangiom; Female; Aged; Adolescent; neovaskularizace choroidey; lidé; Male